Role of Uterine Conservative Surgery in Reproductive Age Group Women: A Retrospective Study - Gohaodkar, Rajshree; Deshdeepak, .; Gupta, Shalini (Highlights on Medicine and Medical Science Vol. 1, 2021)
Introduction: Fibroids are a form of benign tumour that can cause extreme dysmenorrhoea, bleeding, and infertility in women of reproductive age. Fibroids raise the risk of miscarriage, with submucosal and intramural fibroids having a significantly higher incidence of spontaneous abortion and significantly lower rates of live birth. As more women postpone childbirth to their 30s-40s, when fibroids are more symptomatic, there is a greater necessity uterus sparing therapies. Now is a good time to survey current practises and views, given the growing number of treatment choices and evolving care provider profiles. The basic minimally invasive surgical technique for treating various fibroids in patients with AUB is endoscopic myomectomy, with reproductive problems being the most common example. Aims & Objectives: 1) fate of infertile patient after myomectomy 2) type of surgery for uterine conservation 3) fate of technique used. Materials and Methods: This retrospective research included 130 women (ages 20 to 48) who presented with symptomatic fibroids and infertility to Rajdeep endoscopy and IVF centre in Kota. Results: In our research, the highest rate of myoma was found in people aged 20 to 40, and the most prevalent fibroids were intramural 38.46%. After both laparoscopy and abdominal myomectomy, the pregnancy rate has increased to 50-60%. Conclusion: Myomectomy is the most common treatment for women who choose to keep their uterus in current practise. When done by a skilled surgeon, the operation is extremely healthy, with morbidity comparable to a hysterectomy.